Pengaruh Gaya Kepemimpinan Transformasional Dan Pemberian Kompensasi Terhadap Semangat Kerja Pegawai Pada Rumah Sakit Jiwa Tampan Provinsi Riau - Defvi Anggreani; Seno Andri (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
This study aims to determine how much influence transformational leadership style and compensation on employee morale at Tampan Mental Hospital, Riau Province. The method used in this research is quantitative method. This study uses primary data sourced from questionnaires and given to 95 research respondents. The results of the tests carried out show that the transformational leadership style and compensation have a positive and significant effect on employee morale at Tampan Mental Hospital, Riau Province